Optimasi Titik Daya Maksimum Global dan Distorsi Harmonik Arus pada Sistem PV-Inverter menggunakan Algoritma Migrasi Lebah (QHBM) - Muhammad Cahyo Bagaskoro; Aripriharta; sujito; Saodah Omar (Jurusan Teknik Elektro Universitas Andalas, 2025)
This paper investigates the optimization of the Global Maximum Power Point (GMPP) and the simulation of Total Harmonic Distortion of Current (THDI) from an inverter connected to a nonlinear load. THDI variations are analyzed with respect to ambient temperature (T) and solar irradiance (G). The study also highlights how harmonic components negatively affect steady-state voltage stability in photovoltaic (PV) systems. The Queen Honey Bee Migration (QHBM) algorithm is applied to optimize GMPP while minimizing THDI. An off-grid PV-inverter system is modeled in MATLAB/Simulink. The model extracts THDI as a function of temperature and irradiance. Simulations cover irradiance from 794.8 to 994.2 W/m² and temperature from 20.0°C to 32.3°C, based on daily measurements from 08:25 to 16:50. The QHBM algorithm tracks GMPP effectively under fluctuating irradiance. Results show a 17.3% improvement in power extraction efficiency and a 32.8% reduction in THDI compared to conventional methods. The highest THDI occurs during low irradiance, particularly in the early morning and late afternoon. The algorithm converges in 0.18 seconds, outperforming other techniques. THDI increases during rapid irradiance and temperature changes. The proposed method ensures stable performance and lower THDI. Combining QHBM with active harmonic filters under low irradiance conditions is recommended to improve power quality and enhance system protection.